The Perfumery Spices of Dayak Land and Its Trade in the Nineteenth Century - Dana Listiana (LIPI Press, 2021)
The study of spices in Kalimantan area tends to focus on pepper, a commodity that can be said to introducethis island as a ‘pepper country’ to the wider world in the maps made by European explorers. In fact, othercommodities, such as garu (agarwood) and sintok (wild cinnamon), have also been traded long before pepper.As a commodity, the two endemic fragrances that grow naturally in the forest certainly have different effects onthe community than the cultivated pepper. How the mutual influence that binds between the community and theenvironment in the perfume trade is the focus that will be revealed using the historical method with an environmentalhistory approach. Thus, the environment becomes an aspect that is also discussed in changing people’s lives. Thisis different from the study of pepper which focuses more on the political-economic aspects. The results showedthat the production and trade system of perfumery spices is engaged with the values, traditions, and rules of thelocal forester of Dayak as the main actors, both as individuals and groups